Mandated versus Negotiated Severance Pay - Stéphane Auray; Samuel Danthine; Markus Poschke (Institute for the Study of Labor (IZA), 2014)
While most of the literature on employment protection has focused on government-mandated severance pay, it has recently been documented that a substantial share of severance payments derives from private contracts or collective agreements. This paper studies the determination of these payments. We analyze the problem of joint bargaining over wages and severance payments and examine the impact of unions on these choices. To do so, we use a search and matching model with risk averse workers, in which we assume that workers may be unionized and that bargaining is over wages and severance pay. Bargaining results in levels of severance pay providing full insurance, which depend on the generosity of unemployment benefits and on the job finding rate. Unions opt for higher levels of severance pay given that their higher wage demands imply reduced job creation. Calibrated to 8 European economies, the model predicts bargained levels of severance pay which are close to those found in reality.
Keywords: E24; J32; J33; J64; J65; 330; severance pay; unions; bargaining; Diamond-Mortensen-Pissarides models